KEBIJAKAN PERDAGANGAN INTERNASIONAL TERHADAP PELUANG EKSPOR IMPOR NEGARA INDONESIA - Febri Kinanti, Ayunda; Christian Sitohang, Arga; Nadila Rahma, Iluh; Wirastiti, Melinda; Fitriani, Azizatun; Fidzaky, Alif Finno; Safira, Tina; Yelanita, Verinda (LP2M Universitas Bina Bangsa, 2025)
International trade policy can open up opportunities for import-export activities because the wider international trade is believed to be able to accelerate the economic growth of Indonesia and the world economy. The aim of this research is to find out Indonesia's international trade policy towards the global market, especially export and import activities related to all countries in the world, as well as to find out opportunities in international trade for export-import activities in Indonesia.The type of research used is literature study research by reviewing journals related to international trade policy on Indonesian export-import opportunities. This approach includes a number of tasks related to collecting information from library sources, reading, taking notes, and processing research materials. Activities that include international trade are export and import activities carried out across countries.Therefore, international trade policies which also play a key role in shaping the global trade structure, tariffs, quotas, free trade agreements and other trade regulations can provide incentives or obstacles for trade between countries so that there are many export and import opportunities for international trade. maximizing the benefits of international trade policies by minimizing the risks and negative impacts.